Knowledge, attitude, and practices toward dengue fever among the public: a cross-sectional study in the Western region of Saudi Arabia - Hamed, Munerah (Frontiers in Public Health, 2024)
Background: Dengue fever is a primary viral disease transmitted to humans by mosquitoes, imposing a significant economic and health burden in numerous regions globally. There is a lack of studies addressing the importance of health education regarding dengue fever in Saudi Arabia. Therefore, this study aimed to assess predictors influencing knowledge, attitude, and practices of the Western region public in Saudi Arabia related to dengue fever. Methods: This cross-sectional study was conducted as an online self-administered questionnaire collected from July 2023 until August 2023, included 695 participants from the Western region residents aged ≥ 18 years. Data collected involved sociodemographics, participants' knowledge, attitude, and practices toward DF. We presented the descriptive data as mean ± standard deviations (SD) and medians (interquartile range [IQR]) for continuous variables, while categorical variables were presented as frequencies (percent [%]). Results: Good participants' knowledge and attitude toward DF were observed among participants [median score 21.0 (interquartile range 16.0-24.0)] out of 35 and [median score 4.00 (interquartile range 3.00-5.00) out of 5, respectively. Limited participants' practices toward DF were observed among participants [median score 3.0 (interquartile range 0.00-5.00) out of 8]. Participants' knowledge and attitude were not correlated. Participants' education level and employment status predicted participant knowledge of DF. Participants' age, monthly income, employment status and marital status predicted participants' attitude toward DF. Participants' age, marital status, education levels and income predicted participants' practices toward DF. Conclusion: Knowledge, attitude, and practices toward DF among adults in Saudi Arabia can be predicted by specific sociodemographic characteristics. Implementing interferences that focus on improving public practices toward DF is imperative.